Agency Problems in Housing Allowance Expenditure of Local Representatives - Abdullah, Syukriy; Ikrima, Meisi; Nurhasanah, Nurhanasah; Junita, Afrah (Public Accounting and Sustainability, 2025)
Research aims: This study aims to examine how local government size, regional fiscal capacity, and legislative size influence the level of housing allowances allocated to members of regional representative council (DPRD). By doing so, the study seeks to provide empirical evidence on agency problems in local public budgeting, particularly in expenditure items that directly benefit political agents. Design/Methodology/Approach: This study adopts a quantitative approach using a multiple linear regression model. The sample consists of 188 district and municipal governments in Indonesia observed over the period 2017–2023. Secondary data were collected from local government budgets (APBD), audited financial statements, and local regulations governing DPRD allowances. Research findings: The empirical results indicate that local government size, regional fiscal capacity, and the number of DPRD members have a positive and significant effect on the amount of housing allowances received by DPRD members. Theoretical contribution/Originality: This study extends agency theory by demonstrating that, in the context of Indonesian local governments, agency problems are not only driven by information asymmetry but also by structural factors such as fiscal capacity and political scale. The findings confirm that political agents are able to strategically influence budgetary outcomes when institutional control mechanisms are weak, thereby enriching the application of agency theory in decentralized public sector settings. Practitioner/Policy Implication: The determination of DPRD housing allowances should be governed by a nationally standardized upper-limit formula based on objective fiscal indicators and regional cost indices, supported by mandatory independent fiscal reviews prior to approval. Additionally, enhanced transparency through detailed public disclosure of allowance components in APBD documents is essential to strengthen accountability and reduce legislative rent-seeking behavior.